1989
DOI: 10.1002/pssb.2221530210
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectra and Phase Transitions in Layered Semiconducting Ferroelectrics with TlGaSe2 Structure. I. Temperature Dependences of Parameters of the Raman Spectrum Lines of TlGaSe2

Abstract: Yu. I. DURXEV et al.: Vibrational Spectra and Phase Transitions (I)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
(4 reference statements)
2
11
0
Order By: Relevance
“…We have decided that these values (90-100, 100, 100-120, 160-180, 220-240 and 240-250 K) obtained from the band gap energy change may be phase transition temperatures. The presence of phase transition temperature in TlGaSe 2(1−x) S 2x at some temperatures given Table II was also confirmed by temperatures given in the literature [14,[23][24][25][26][27][28].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We have decided that these values (90-100, 100, 100-120, 160-180, 220-240 and 240-250 K) obtained from the band gap energy change may be phase transition temperatures. The presence of phase transition temperature in TlGaSe 2(1−x) S 2x at some temperatures given Table II was also confirmed by temperatures given in the literature [14,[23][24][25][26][27][28].…”
Section: Resultssupporting
confidence: 74%
“…The dielectric and optical anomalies of TlGaSe 2 indicate structural changes at T ∼ = 120 K and 107 K [14,24]. The presence of the phase transitions at 246 K and 101 K were confirmed by means of the heat capacity measurement [25,26]. The temperature dependence of C p of TlGaS 2 single crystal was obtained in the range 60-260 K during heating.…”
Section: Introductionmentioning
confidence: 72%
“…The long-wavelength tail of the optical absorption in TlGaSe 2 at a ¼ 30-150 cm --1 is shown to obey the Urbach rule in the temperature range 4.2-293 K [8,9]. The anomalous behaviour of the parameters of this rule suggests the presence of two phase transitions in TlGaSe 2 at 246 and 101 K in addition to the known phase transitions at 120 and 107 K. The presence of the phase transitions at 246 and 101 K is also confirmed by means of heat capacity measurement [8,9].…”
Section: Introductionsupporting
confidence: 91%
“…Since the structure of A 3 B 3 C 6 layer crystals, such as TlGaSe 2 , TlGaS 2 , TlInSe 2 and TlInS 2 were generally assigned as tetragonal or monoclinic with space group C 6 2h , and its pseudotetragonality was attributed to the presence of micro twins [4,20]. It was reported that this ambiguity of this class of compounds may also be related with different possible versions of layer stacking [2].…”
Section: Resultsmentioning
confidence: 97%
“…But most of them are focused on the study of phase transitions of these layer crystals, such as TlGaSe 2 [4], TlGaS 2 [4,5], and TlInS 2 [2,[6][7][8]. The crystallographic data on these compounds have been ambiguous * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%